PECULIARITIES OF LIPID METABOLISM DISORDERS IN NORMOTENSIVE PERSONS WITH BURDENED HEREDITY FOR HYPERTENSION AND PATIENTS WITH STAGE II HYPERTENSION - Kuzminova, N.V.; Romanova, V.O.; Ivankova, A.V.; Lozinsky, S.E.; Kniazkova, I.I.; Shkarivskyi, Yu.L.; Poberezhets, O.L. (World of Medicine and Biology, 2024)
The article presents the results of a study of lipid metabolism in healthy individuals with a burdened heredity for arterial hypertension and patients with stage II hypertension. Lipid metabolism was studied using standard lipidogram parameters, with additional determination of apolipoproteins B100 and A-1 and lipoprotein (a). It was noted that in the blood serum of healthy individuals with a burdened heredity for arterial hypertension, proatherogenic changes in lipid fractions occur, similar to those of patients with stage II hypertension. It is noteworthy that the level of Lp(a) in individuals with a hereditary predisposition to hypertension was 67.0 % higher than in the control group (p